Implementation of the Marriage Management Information System Policy Ministry of the Republic of Indonesia - Atmaja, Agus; Rohayati, Yeti; Kamil, Indriyati; Indah, Diani (Global Education Journal, 2025)
Digital transformation in public services is a crucial phenomenon in the modern era of governance, which demands efficiency, transparency, and accountability. One effort undertaken by the Ministry of Religious Affairs of the Republic of Indonesia is the implementation of the Marriage Management Information System (SIMKAH), which is expected to improve the quality of marriage registration services across all Religious Affairs Offices (KUA). This study aims to analyze the implementation of SIMKAH at the KUA in Ciparay District, Bandung Regency, by examining supporting factors, obstacles, and its impact on public services. A qualitative case study approach was used, collecting data through interviews, observations, and documentation studies. The data were then analyzed using George C. Edwards III's policy implementation model, which encompasses aspects of communication, resources, disposition, and bureaucratic structure, and is supported by theories of good governance and e-government. The results indicate that the implementation of SIMKAH has brought positive changes in terms of service efficiency, data accuracy, and transparency in administrative processes. However, it faces challenges such as limited digital infrastructure, technological literacy, and resistance from some members of the public to the use of new technologies. This study recommends increasing human resource capacity, strengthening technological infrastructure, and implementing a more intensive outreach strategy to maximize SIMKAH's future use.